2021
DOI: 10.1096/fj.202002350r
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor deficiency causes the development of chronic obstructive pulmonary disease through the integration of multiple pathogenic mechanisms

Abstract: Emphysema, a component of chronic obstructive pulmonary disease (COPD), is characterized by irreversible alveolar destruction that results in a progressive decline in lung function. This alveolar destruction is caused by cigarette smoke, the most important risk factor for COPD. Only 15%‐20% of smokers develop COPD, suggesting that unknown factors contribute to disease pathogenesis. We postulate that the aryl hydrocarbon receptor (AHR), a receptor/transcription factor highly expressed in the lungs, may be a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Therefore, these results provide evidence for the first time that the AhR is a biological pathway that reduces their formation in the lungs. Although we speculate that the ability of the AhR to prevent formation of MNGCs contributes to suppression of the emphysema-like phenotype (Guerrina et al, 2021), a limitation of our study is that we did not directly address whether MNGCs contribute to smoke-induced lung damage. We also did not evaluate how the AhR controls their formation or identify the cellular precursor(s).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, these results provide evidence for the first time that the AhR is a biological pathway that reduces their formation in the lungs. Although we speculate that the ability of the AhR to prevent formation of MNGCs contributes to suppression of the emphysema-like phenotype (Guerrina et al, 2021), a limitation of our study is that we did not directly address whether MNGCs contribute to smoke-induced lung damage. We also did not evaluate how the AhR controls their formation or identify the cellular precursor(s).…”
Section: Discussionmentioning
confidence: 99%
“…However, the AhR has emerged as a critical component of immunity, dampening the severity of diseases associated with chronic inflammation such as rheumatoid arthritis (Rosser et al, 2020;Nehmar et al, 2021), inflammatory bowel disease (Riemschneider et al, 2021), asthma (Chang et al, 2020), periodontitis (Huang et al, 2019), psoriasis (Di Meglio et al, 2014) and multiple sclerosis (Abdullah et al, 2019). We have previously shown that the AhR attenuates pulmonary neutrophilia in response to acute and sub-chronic cigarette smoke exposure (Thatcher et al, 2007;de Souza et al, 2014;Rico de Souza et al, 2021) and prevents the development of a COPD-like phenotype (Guerrina et al, 2021). However, it remains unknown whether the AhR can reduce inflammation caused by chronic cigarette smoke exposure, findings that are relevant given that people who develop COPD often smoke for decades.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, some of these factors are AHR active and can impair airway homeostasis via the AHR genomic pathway [ 19 , 27 ]. Additionally, these factors might ablate the AHR content [ 27 ], which is frequently seen in aging [ 28 ] and COPD [ 29 , 30 ]. In this study, we confirmed that patients with emphysema and chronic lung inflammation have a significant reduction in AHR in pulmonary cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we confirmed that patients with emphysema and chronic lung inflammation have a significant reduction in AHR in pulmonary cells. After chronic exposure to cigarette smoke, AHR-KO mice develop airspace enlargement concomitant with a decline in lung function [ 30 ], suggesting that loss of AHR may be a susceptibility factor for COPD. The healing of airway epithelium requires complex processes involving the spreading and migration of healthy epithelial cells from neighboring sites, cell proliferation, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…This complex binds to DNA sequences termed the dioxin response element (DRE), initiating the transcription of genes that comprise the AhR gene battery such as cytochrome P450 (CYP) enzymes ( Guerrina et al, 2018 ). Although historically, the AhR has been largely associated with xenobiotic metabolism leading to toxicity, we have shown that the AhR suppresses the development of chronic obstructive pulmonary disease (COPD; Guerrina et al, 2021 ), an obstructive lung disease caused predominantly by cigarette smoke. Mechanistically, the AhR also suppresses neutrophil recruitment to the lungs in response to cigarette smoke ( Thatcher et al, 2007 ; De Souza et al, 2014 ; Rico De Souza et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%